RHETORICAL MOVES ON THE BBC NEWS ABOUT THE UNITED STATES OF AMERICAN PRESIDENT, JOSEPH BIDEN, IN ANNOUNCING OF OIL BANNING OVER UKRAINE - Ali - Amran (UIN Sumatera Utara, 2022)
The objective of this study is to find out the functions of rhetocial moves and to find out the negative effects of rhetorical moves by Josep Biden. This research used the qualitative design. The data source of this research is the script that will be taken from Youtube channel. The channel containes news about the United States of American President, Joseph Biden, in announcing of oil banning over Ukraine conflict.The research shows that there are three distinct registers, namely the